Debt and Economic Growth Nexus in the US: Evidence from Asymmetric Casuality - GÜMÜŞOĞLU, NEBİLE KORUCU (11. Uluslararası İstatistik Kongresi, 2019)
The relationship between economic growth and debt has been studied for decades. This (casual) relationship can be different according to debt types, regions and countries. In this sense, the main motivation of this study is to find out if there is a casual relationship. Moreover, we aim to analyze the nonlinearity between economic growth and debt for the US. This asymmetric relationship is analyzed by vector error correction model. Preliminary results show that there is an asymmetric causality for debt and growth.
Keywords: Debt; Growth; Asymmetry; Vector Error Correction Model; Turkey; Borç; Büyüme; Asimetri; Türkiye